Pengaruh Orientasi Kewirausahaan dan Pasar terhadap Kinerja Usaha Cafe di Kota Langsa - Ryandi Rivanda; Iskandar; Mutia Sumarni (JIM: Jurnal Ilmiah Mahasiswa, 2022)
The development of a Kafe business is inseparable from the existence of consumers who still want to visit it. This gives enthusiasm for those who have an entrepreneurial orientation to become entrepreneurs in the Kafe business. This research was conducted with the aim to determine the effect of entrepreneurial orientation and market orientation on the business performance of Kafe in Langsa City. This study uses primary data with a sample size of 103 respondents. The data analysis method used is multiple linear regression equation, the coefficient of determination (R2) and hypothesis testing using the t test and F test. The results obtained Y = 2.198 + 0.239X1 + 0.478X2. These results indicate that the Kafe business performance is 2.198 before being influenced by entrepreneurial orientation and market orientation, while the regression coefficient of entrepreneurial orientation and market orientation has a positive and unidirectional influence on the performance of Kafe businesses in Langsa City. The coefficient of determination test results of 50.4%, the entrepreneurial orientation and market orientation variables can explain the cafe business performance variables. The results of the entrepreneurial orientation t test, t count> t table (5.707> 1.983) and the tsig value <α 5% (0.00 <0.05), market orientation tcount> t table (5.220> 1.983) and the tsig value <α 5% (0.000 <0.05), it can be stated partially that entrepreneurial orientation and market orientation have a significant effect on business performance. Thus the results of the F test, Fcount> Ftable (50.746> 3.09) and the Fsig value <α 5% (0.000 <0.05), it can be stated that simultaneously entrepreneurial orientation and market orientation have a significant effect on business performance.